miR-200a-3p- and miR-181-5p-Mediated HOXB5 Upregulation Promotes HCC Progression by Transcriptional Activation of EGFR - Li, Weizhi; Li, Yingchao; Li, Peijie; Ma, Fuquan; Liu, Mengying; Kong, Shuzhen; Xue, Hui (Frontiers in Oncology, 2022)
Abstracts Background HCC remains worldwide burden. However, the mechanisms behind the malignant biological behavior of HCC remains unclear. The homeobox (HOX) family could act as either promoters or suppressors in different kinds of malignancies. Our study discovered the role of HOXB5 in regulating HCC progression. Methods The HOXB5 expression was assessed by RT-PCR analysis in human HCC samples and cell lines. HOXB5 transcriptional regulation of the EGFR was verified by the luciferase reporter assay and chromatin immunoprecipitation experiment. The oncogenic role of HOXB5 in HCC progression were analyzed by CCK8, colony-forming and transwell assays. Results Upregulation of HOXB5 was found in human HCC, and was strongly correlated with HCC tumor size, tumor-nodule metastasis, TNM stage, relatively unfavorable OS and DFS. Ectopic expression of HOXB5 promoted the capacity of cell growth and clonogenicity, while the inhibition of HOXB5 decreased the proliferation and clonogenicity potential in vitro by CCK8 and colony-forming assays. In addition, HOXB5 also promoted cell migration by transwell experiment. Mechanism studies elucidated that HOXB5 trigger HCC progression via directly transcriptional activation of EGFR. The upregulation of HOXB5 is regulated by miR-200a-3p and miR-181-5p. Transfection of miR-200a-3p and miR-181-5p mimics blocked the cell proliferation and migration regulated by HOXB5, while overexpression of the 3′-UTR mutant HOXB5 abolished the suppressive effect of miR-200a-3p and miR-181-5p, but not the wild-type HOXB5. Conclusion HOXB5 is a promising prognostic factor in human HCC. Targeting miR-200a-3p and miR-181-5p/HOXB5/EGFR signaling pathway may provide new options for the treatment strategies of HCC.